2012
DOI: 10.6002/ect.2012.0079
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Nephrectomy in Morbidly Obese Donors

Abstract: Conclusions:The limited data suggest that nephrectomy may be feasible in selected morbidly obese donors. Further study is needed before major conclusions can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Various other studies have reported on the feasibility of live kidney donation from obese donors. 33,[68][69][70][71][72][73][74][75][76][77][78][79] Recommendation. On the basis of the available literature, we conclude that the selection of potential kidney donors should not be based on BMI alone.…”
Section: Obesitymentioning
confidence: 99%
“…Various other studies have reported on the feasibility of live kidney donation from obese donors. 33,[68][69][70][71][72][73][74][75][76][77][78][79] Recommendation. On the basis of the available literature, we conclude that the selection of potential kidney donors should not be based on BMI alone.…”
Section: Obesitymentioning
confidence: 99%